Elusive structural changes of New Delhi metallo-β-lactamase revealed by ultraviolet photodissociation mass spectrometry. Issue 33 (17th August 2020) - Mehaffey, M. Rachel; Ahn, Yeong-Chan; Rivera, Dann D.; Thomas, Pei W.; Cheng, Zishuo; Crowder, Michael W.; Pratt, R. F.; Fast, Walter; Brodbelt, Jennifer S.
Abstract : We use mass spectrometry (MS) along with ultraviolet photodissociation (UVPD) to characterize structural variations in New Delhi metallo-β-lactamase (NDM) upon perturbation by ligands or mutation. Abstract : We use mass spectrometry (MS), under denaturing and non-denaturing solution conditions, along with ultraviolet photodissociation (UVPD) to characterize structural variations in New Delhi metallo-β-lactamase (NDM) upon perturbation by ligands or mutation. Mapping changes in the abundances and distributions of fragment ions enables sensitive detection of structural alterations throughout the protein. Binding of three covalent inhibitors was characterized: a pentafluorphenyl ester, an O -aryloxycarbonyl hydroxamate, and ebselen. The first two inhibitors modify Lys211 and maintain dizinc binding, although the pentafluorophenyl ester is not selective (Lys214 and Lys216 are also modified). Ebselen reacts with the sole Cys (Cys208) and ejects Zn2 from the active site. For each inhibitor, native UVPD-MS enabled simultaneous detection of the closing of a substrate-binding beta-hairpin loop, identification of covalently-modified residue(s), reporting of the metalation state of the enzyme, and in the case of ebselen, observation of the induction of partial disorder in the C-terminus of the protein. Owing to the ability of native UVPD-MS to track structural changes and metalation state with high sensitivity, we further used this method to evaluate the impact of mutations found in NDM clinical variants. Changes introduced by NDM-4 (M154L) and NDM-6 (A233V) are revealed to propagate through separate networks of interactions to direct zinc ligands, and the combination of these two mutations in NDM-15 (M154L, A233V) results in additive as well as additional structural changes. Insight from UVPD-MS helps to elucidate how distant mutations impact zinc affinity in the evolution of this antibiotic resistance determinant. UVPD-MS is a powerful tool capable of simultaneous reporting of ligand binding, conformational changes and metalation state of NDM, revealing structural aspects of ligand recognition and clinical variants that have proven difficult to probe.